2014
DOI: 10.1002/pbc.25288
|View full text |Cite|
|
Sign up to set email alerts
|

Why pediatric patients with cancer visit the emergency department: United States, 2006–2010

Abstract: BACKGROUND Little is known about emergency department (ED) use among pediatric patients with cancer. We explored reasons prompting emergency department (ED) visits and factors associated with hospital admission. PROCEDURE A retrospective cohort analysis of pediatric ED visits from 2006-2010 using the Nationwide Emergency Department Sample, the largest all-payer database of United States ED visits. Pediatric patients with cancer (ages ≤19 years) were identified using Clinical Classification Software. Proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 21 publications
2
108
0
Order By: Relevance
“…3 Children with cancer who are self-pay are more likely to be discharged than those with public or private insurance. 4 Whether the primary drivers of disposition decisions in the above cases are analogous to those in cases of physical abuse is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Children with cancer who are self-pay are more likely to be discharged than those with public or private insurance. 4 Whether the primary drivers of disposition decisions in the above cases are analogous to those in cases of physical abuse is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, less is known about how the association between insurance type and disposition extends to the vulnerable population of young abused children. Children younger than 2 years of age account for approximately one-fifth of cases of child maltreatment and over 60% of child fatalities from abuse.…”
mentioning
confidence: 99%
“…It's patterned on a similar analysis of pediatric patients that was published in late 2014. 1 That study found that fever and febrile neutropenia were the most common diagnoses in the ED, accounting for about 20% of visits, and up to 82% of the patients with febrile neutropenia ended up being admitted to the hospital.…”
Section: Defining the Problemmentioning
confidence: 97%
“…This group used a multistep process for stratifying cancer-related admissions into four categories: chemotherapy-related, procedure-related, infection-related, or toxicity-related. Similarly, Mueller et al described the use of CCS to describe the reasons for emergency department visits among pediatric cancer patients, including risk factors for admission to the hospital [34]. …”
Section: Tools To Enhance Large Dataset Analysismentioning
confidence: 99%